AUDIT FEES AND COMPANIES’ ACCESS TO FINANCE - Devi Sulistyo Kalanjati; Reyhan Ario Bramantio (Berkala Akuntansi dan Keuangan Indonesia, 2023)
This paper aims to study the impact of audit fees on companies' ability to access finance by reducing their capital constraints. This study employs a dataset of listed non-financial Indonesian companies from 2016 to 2020. Unlike previous studies, which mostly examined this phenomenon in developed economies, this paper focuses on a country with a two-tier corporate governance model where the capital market is not a major source of financing and the disclosure of audit fees is still voluntary. In such a setting, the decision to disclose audit fees is in the hand of the companies' management, and various motivations behind the decision will differently impact different users of financial information. This paper focuses on whether the information related to audit fees is a good signal for capital providers. Following the limited attention theory, this study argues that capital providers will consider the information about audit fees as a more reliable proxy for audit efforts that subsequently affect their investment decision. The hypothesis is that audit fees are negatively associated with companies' financial constraints. The findings indicate that capital providers see higher audit fees as signals of high-quality audits that enhance the credibility of financial statements and positively impact companies' access to finance. Key Words: Audit Fees, Capital Constraint, Access to Finance, Audit Quality, Limited Attention Theory